Evaluation of Swanirvar Programme in five villages of Mithapukur Thana, [Rangpur] - Bazlul Karim, Kazi (Rural Development Academy, 1976)
On the community development program in the villages of Batasan Durgapur, Askarpur, Genarpara, Musapur, and Paikpara.